Turning student assignments into publications: Benefits for librarians and students - MacDonald, Heather (Journal of EAHIL, 2022)
This article describes librarian involvement in a graduate student assignment to conduct rapid scoping reviews. Students had the option to submit a manuscript for publication. The librarian role through assignment conception to publication is detailed. The benefits for both students and the librarian are discussed.